A Facies Approach to the Stratigraphic Analysis of Late Wisconsinan Sediments in the Portal Creek Area, Jasper National Park, Alberta - Levson, Victor; Rutter, Nathaniel (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1986)
ABSTRACTGlacial diamictons described and sampled during regional stratigraphie studies in Jasper National Park, Alberta, Canada, are categorized using a facies approach. The classification scheme is based on objective field criteria but it is designed to ultimately aid in genetic interpretations of the described deposits which are required for meaningful stratigraphie correlations. The utility of the facies approach in solving stratigraphie problems is tested by the analysis of a complex sequence of glacial diamictons in the Portal Creek area. Genetic interpretations placed on the facies were supported by general agreement between theoretical and observed facies sequences, and proved useful in solving stratigraphie problems. Stratigraphic and provenance studies in the Portal Creek region reveal three major sediment packages of distinct provenance indicating that three separate glacial episodes may have occurred. However, an environment analysis of the deposits shows that the oldest two groups of sediment probably were deposited during the same episode. Changes in till provenance are believed to be the result of fluctuations in the dominance of two confluent glaciers originating in different valleys. The facies analysis supports the stratigraphie evidence that the third sedimentary package was deposited in a distinct glacial episode at a significantly later time than the underlying deposits. Although stratigraphie correlations with dated sediments are tentative, both glacial events recorded in the Portal Creek strati-graphic record are presumed to be Late Wisconsinan in age.